The PENGEMBANGAN BAHAN AJAR IPAS TERINTEGRASI MODEL RADEC DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR: Penelitian Pengembangan - Erlinda, Rosni; Angelia, Inge; Sudirman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT Education in 21st century must be able to produce the next generation that have critical thinking skill to solve their problem in the daily life. Knowledge and technology develop quickly, that why the government make changes in education. One of the changes that the government do is adjust curriculum with the progress of time. The changes of curriculum requires teacher to prepare teaching activities that suitable with student’s needs. At this time, we need generation that have critical thinking, independent, creative, and can fulfill their own daily life. Because of that, the teacher must be able to prepare teaching material to support curriculum, student’s need. The teaching material model RADEC one of the way to improve students critical thinking. It’s support the students participate active in the class activities. The purpose of the research is to develop IPAS teaching material integrated model RADEC to improve student’s critical thinking. The research is research dan development (R&D). The steps of development is 4-D model, the steps are define, design, develop, dan disseminate. The research get quantitative and qualitative data. Quantitative is gotten from observations and interview. On the other hand, qualitative data is gotten form students responses, teachers responses, validator, learning outcomes, critical thinking students skill. The research show that development of teaching material model RADEC can increase student’s critical thinking Key words : Teaching Material, Model RADEC, Critical Thinking